A Comparative Clinical Study To Assess The Effect Of Dhurdhurapatradi Taila And Malatyadi Taila Shirodhara In Darunaka - Narayan, Hosmani Trupti; Ashok, Kulkarni Ashwini; Raviprasad; Bhat, Roopa (International Research Journal of Ayurveda & Yoga, 2020)
Darunaka is common problem of the scalp and hair in all age group, either sex. It is a Vata Kapha predominant condition and Kandu, Twaksphutana, Shirorukshata and Keshachyuti are the symptoms explained in classics. Different procedures and medication like Shirodhara, Shirobasti, Shiroabhyanga, and Shirolepa etc. are mentioned in Ayurveda for the treatment of the disease Darunaka. A total number of 40 patients were selected for the study and divided into two equal groups of 20 patients each and subjected to Dhurdhurapatradi Taila Shirodhara and Malatyadi Taila Shirodhara respectively. Both Dhurdhurapatradi taila and Malatyadi taila Shirodhara showed significant relief in the Darunaka, especially in lakshanas like Kandu and Twaksphutana.